Aortic valve repair using pericardial patch standardized with external ring annuloplasty. (15th February 2022) - Danial, Pichoy; Moiroux-Sahraoui, Alexander; Debauchez, Mathieu; Monin, Jean-Luc; Berrebi, Alain; Shraer, Nathanael; Lansac, Emmanuel
Abstract: OBJECTIVES: This study was undertaken to analyse outcomes of aortic valve repair using additional material and compare the results to those of cusp repair without the use of the pericardial patch. METHODS: All consecutive patients aged over 16 who underwent aortic valve repair with external ring annuloplasty for isolated aortic insufficiency, aortic insufficiency and tubular aortic aneurysm or aortic root aneurysm between May 2003 and November 2019 were included in a cohort study. Data were collected and analysed from the AVIATOR registry (AorticValve repair InternATiOnal Registry). Propensity score framework analysis (inverse probability of treatment weighting) was used to compare outcomes of the groups while controlling for confounders. RESULTS: During the 16-year study period, 618 patients underwent aortic valve repair. Eight-year survival rate was 92% in the patch group and 90.2% in the no patch group without significant differences [ P = 0.957 inverse probability of treatment weighting (IPTW) weighted]. Early valve-related reoperation was more frequent in the patch group as compared to the no patch group (6% vs 1%, P < 0.001 IPTW weighted), the freedom from aortic valve-related reintervention and from structural valve deterioration at 8 years was not significantly different between the patch and no patch groups (93.7% vs 94%, P = 0.968 IPTW weighted; and 99.3% vs 96.7%, P = 0.964 IPTW weighted). CONCLUSIONS: Although a higher rate of early reintervention was observed, aortic valve repair using the pericardial patch, in a standardized approach using external annuloplasty, with effective coaptation height of at least 9 mm, was not associated with an increase in mid-term aortic valve-related reoperation or structural valve deterioration as compared to valve repair without the pericardial patch. Abstract : Aortic valvuloplasty techniques for aortic insufficiency (AI) are becoming more and more standardized allowing good long-term results with low rates of valve-related events [1–3].